Solving Equations Using Polar Coordinates - Anvar oʻgʻli, Abdullayev Sarvar (Journal of Higher Education and Academic Advancement, 2024)
This work is dedicated to solving some equations of elementary mathematics using the polar coordinate system. In mathematics, solving some equations in the usual way causes us a number of problems, and solving such equations using the polar coordinate system helps us find the answer much easier. The article first gives information about the polar coordinate system and shows several examples.